Anti-PTSD Effects of Hypidone Hydrochloride (YL-0919): A Novel Combined Selective 5-HT Reuptake Inhibitor/5-HT1A Receptor Partial Agonist/5-HT6 Receptor Full Agonist - Liu, Wen-Gang; Zhang, Li-Ming; Yao, Jun-Qi; Yin, Yong-Yu; Zhang, Xiao-Ying; Li, Yun-Feng; Cao, Jiang-Bei (Frontiers in Pharmacology, 2021)
Posttraumatic stress disorder (PTSD) is a debilitating anxiety disorder that has become a major neuropsychiatric problem, leading to substantial disruptions in individual health and societal costs. Our previous studies have demonstrated that hypidone hydrochloride (YL-0919), a novel combined selective 5-HT reuptake inhibitor/5-HT1A receptor partial agonist/5-HT6 receptor full agonist, exerts notable antidepressant- and anxiolytic-like as well as procognitive effects. However, whether YL-0919 exerts anti-PTSD effects and its underlying mechanisms are still unclear. In the present study, we showed that chronic treatment with YL-0919 caused significant suppression of contextual fear, enhanced anxiety and cognitive dysfunction induced by the time-dependent sensitization (TDS) procedure in rats and by inescapable electric foot-shock in a mouse model of PTSD. Furthermore, we found that repeated treatment with YL-0919 significantly reversed the accompanying decreased expression of the brain-derived neurotrophic factor (BDNF) and the synaptic proteins (synapsin1 and GluA1), and ameliorated the neuroplasticity disruption in the prefrontal cortex (PFC), including the dendritic complexity and spine density of pyramidal neurons. Taken together, the current study indicated that YL-0919 exerts clear anti-PTSD effects, which might be partially mediated by ameliorating the structural neuroplasticity by increasing the expression of BDNF and the formation of synaptic proteins in the PFC.